Water-Borne Perovskite Quantum Dot-Loaded, Polystyrene Latex Ink - Huang, Keke; Peng, Lucheng; Liu, Baijun; Li, Dongze; Ma, Qiang; Zhang, Mingyao; Xie, Renguo; Wang, Dayang; Yang, Wensheng (Frontiers in Chemistry, 2018)
Quantum dot, lead halide perovskites, luminescence, water-borne ink, polystyrene Abstract: Highly lipophilic quantum dots (QDs) of cesium lead halides were successfully embedded in polystyrene (PS) particles by deliberately controlling the swelling of the PS particles in the mixtures of the good and bad organic solvents. The resulting composite particles were readily transferred into water via simple stepwise solvent exchange, yielding water-borne, perovskite QD-based inks with outstanding structural and chemical stability in aqueous media. Little change in the photoluminescence (PL) of the QDs loaded in the polystyrene particles was visible after 1 month incubation of the composite particles in water in a broad pH range from 1 to 14, which is hardly realized otherwise thus far. Yet loading into the PS particles makes the QDs being fairly stable against polar organic solvents such as ethanol, intense light irradiation, and heat; the QD PL intensity remains little changed after the composite particles were heated at 75 oC and under irradiation of strong blue light (@365 nm) for 1 h. Furthermore, the PS matrices can effectively inhibit the exchange of halide anions between two differently-sized perovskite QDs loaded therin, thus offering great technical advantage in application of multiple perovskite QDs for multi-color display for instance in future.